Biologia reprodutiva de Dipsas neivai Amaral e D. catesbyi (Sentzen) (Serpentes, Colubridae) no sudeste da Bahia, Brasil - Alves, Fátima Q.; Argolo, Antônio J.S.; Jim, Jorge [UNESP] (Sociedade Brasileira de Zoologia, 2005)
A biologia reprodutiva de Dipsas neivai Amaral, 1923 e Dipsas catesbyi (Sentezen, 1796) foi estudada através da dissecção de 261 espécimes de D. neivai e 222 de D. catesbyi. em D. neivai o macho amadurece com menor tamanho do que a fêmea, ocorrendo o oposto em D. catesbyi. em ambas as espécies a fêmea atinge maior tamanho corporal que o macho. O tamanho da ninhada variou de um a oito ovos em D. neivai e de um a seis em D. catesbyi, não estando correlacionado com o tamanho da fêmea na última. O ciclo reprodutivo em ambos machos e fêmeas é contínuo, com vitelogênese e espermatogênese ocorrendo ao longo do ano todo. em Dipsas neivai, a cópula nas fêmeas é dissociado da vitelogênese. D. neivai e D. catesbyi são sintópicas, e reproduzem no mesmo período do ano, o que possivelmente está relacionado à disponibilidade contínua de presas e à pouca variação climática no sudeste da Bahia.

The reproductive biology of Dipsas neivai Amaral, 1923 and Dipsas catesbyi (Sentzen, 1796), was studied by dissecting 261 specimens of D. neivai and 222 of D. catesbyi. In D. neivai males mature at smaller body size than females, and in D. catesbyi the opposite was observed. The females were larger than males in both species. The clutch size ranged from one to eight in D. neivai, and one to six in D. catesbyi, but it is not correlated with female length in the last one. Reproductive cycles in both males and females are aseasonal, with vitelogensis and spermatogenesis occurring throughout the year. The couple in females of D. neivai is dissociated from the vitellogenesis. D. neivai and D. catesbyi are syntopic and reproduce in the same time of the year, which is possibly related to the continuous availability of prey and little climate variation in southern Bahia.
Reproductive biology in Dipsas neivai and D. catesbyi (Serpentes, Colubridae) in southeastern Bahia, Brasil
Keywords: Ciclo gonadal; dimorfismo sexual; Floresta Atlântica; maturidade sexual; Atlantic forest; gonadal cycle; sexual dimorphism; sexual maturity